2004
DOI: 10.1093/jnci/djh305
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Proton Pump Inhibitor Pretreatment on Resistance of Solid Tumors to Cytotoxic Drugs

Abstract: Our results open new possibilities for the treatment of drug-resistant tumors through combination strategies based on the use of well-tolerated pH modulators such as PPIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
377
0
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 395 publications
(405 citation statements)
references
References 40 publications
19
377
0
6
Order By: Relevance
“…This sensitization could involve the inhibition of the H þ -ATP synthase by resveratrol (48). Similarly to the proton pump inhibitor omeprazole (49), resveratrol could affect the lysosomal function and reduce cell environment acidity, thereby facilitating the drug activity (50). Interestingly, Parolini and colleagues have described that acidity may also change the lipid composition of tumor cell membrane and consequently play an important role in the internalization of exosomes in tumor cells (51).…”
Section: Discussionmentioning
confidence: 99%
“…This sensitization could involve the inhibition of the H þ -ATP synthase by resveratrol (48). Similarly to the proton pump inhibitor omeprazole (49), resveratrol could affect the lysosomal function and reduce cell environment acidity, thereby facilitating the drug activity (50). Interestingly, Parolini and colleagues have described that acidity may also change the lipid composition of tumor cell membrane and consequently play an important role in the internalization of exosomes in tumor cells (51).…”
Section: Discussionmentioning
confidence: 99%
“…Although deployed as H + /K + ‐ATPase inhibitors, PPI such as omeprazole and esomeprazole, also inhibit V‐ATPase and can increase sensitivity to chemotherapeutics in vitro and in vivo 89, 90. However, it should be noted that the concentration of PPI's required to inhibit V‐ATPase is considerably higher than for H + /K + ‐ATPase 91…”
Section: V‐atpase As a Potential Cancer Therapeutic Targetmentioning
confidence: 99%
“…Involvement in tumour cell resistance to chemotherapy (V-ATPase and drug transporters) [58,65] Role in autocrine signals to neighbouring tumour cells (TNF-α / TNF receptors; mRNA, microRNA) [25,57] Role in autocrine signals to distant tumour cells Effects on different components of the anti-tumour immune response ( FasL, TN F-, TGF-) [25,26,34] Promoting effects on tumour neo-angiogenesis and stromal remodelling (Tetraspanins→VEGF) [56] Figure 3 The hypothesis of pleiotropic role of tumour-secreted exosomes on host environment. On the basis of the different molecules expressed in human tumoursecreted microvesicles, it could be hypothesized that exosomes can be involved in (1) promoting autocrine signalling to neighbouring and distant tumour cells (for their expression of growth factors and cognate receptors); (2) suppressing and deviating immune responses at different cell levels (for their expression of proapoptotic molecules and inhibitory cytokines); (3) favouring neoangiogenesis and stromal remodelling (as they transport tetraspanins that can induce expression of VEGF, matrix metalloproteinase (MMP)); (4) mediating resistance to chemotherapeutic drugs (as their accumulation into vesicular compartments by drugs transporters, to be then eliminated by vesicle shedding).…”
Section: Microvesicles or Exosomesmentioning
confidence: 99%
“…Indeed, we have shown that inhibition of this pathway through proton pump inhibitors (PPIs) interferes with traffic of acidic vesicles, resulting in their sequestration within the cytoplasm, and improving chemosensitivity in melanoma cells. 65 This suggests that anti-acidic treatment may interfere with exosome release and consequently be a potential factor limiting the harmful effects that these microvesicles exert on the immune system. Interestingly, treatment with PPIs leads to apoptotic cell death of tumour cells when utilized at high dose as single agent.…”
Section: Pharmacological Modulation Of Exosome Secretion By Tumour Cellsmentioning
confidence: 99%